Ekspresi Pengalaman Perempuan Pada Novel Layangan Putus Karya Mommy Asf (Kajian Ginokritik) - Rusfita Sari; Yessi Fitriani; Puspa Indah Utami (Departement of Mathematics Education, 2023)
The femininity described by male authors through female characters is not very specific. The characteristics of women writers will only be conveyed through the work of women writers. Literary works produced by female writers are different from literary works produced by male writers, so if they do not use an analysis devoted to women's works then the interpretation will likely not match the author's intentions. Through the study of gynocritics, this study seeks and understands women's issues using texts related to the expression of women's experiences produced by women writers. This study aims to gain a deep understanding of women in the novel Layangan Putus by Mommy ASF in terms of Gynocritic studies. This research method is a content analysis method through a gynecological study. The results of this study showed that the authors expressing women's experiences from women's biology and women's psychology found a total of 48 citations related to the study. The characters studied are the expressions of her experiences, namely three female characters including characters named Kinan, Mama Kinan, and Aris's second wife.